LOKALITAS DAN NASIONALISME: RUANG ALTERNATIF ANTIKOLONIAL DALAM NOVELTHE INHERITANCE OF LOSS KARYA KIRAN DESAI - Nurhidayah, Sri (Jurnal Pena Indonesia, 2019)
Novel The Inheritance of Lossputs spotlightat Biju. He is often narrated to be an ambivalent character and he always receives a negative status with regard to his identity, but Desai brought this character to safe haven with a nationalist attitude. The research problem refers to how the narrative of Biju, whosufferedin the West and brought back to the East, is seen as an image of locality and nationalism. This study uses Sara Upstones theory of spatial politics. The technique of analysis is descriptive interpretation. The result shows that Biju in The Inheritance of Loss is often narrated to be an ambivalent character and he always receives a negative status regarding his identity, but when it is seen from the way Desai narrates the resolution of the Bijus conflict, it implies a nationalist side through locality. Returning to the East is the best way, or alternative space, to release the chaos of Bijus life.